Assessing the reporting quality of systematic reviews and meta-analysises in the Iranian journals of Nursing and Midwifery - Faezeh Ghafoori; Mahshid Taheri; Afrouz Mardi; Nasrin Sarafraz; Reza Negarandeh (Tehran University of Medical Sciences, 2015)
Background & Aim: In the view of the importance of evidence-based clinical practice in recent years, clinical disciplines such as nursing and midwifery have found a special need to systematic review and meta-analysis. However, systematic reviews and meta-analysises like any other studies may be poorly designed and implemented. Therefore, certain guidelines have been considered for reporting of such studies. The PRISMA statement is one of the most recent developments to improve the reporting quality of systematic reviews. The present study aimed to assess the reporting quality of systematic reviews and meta-analysises in the Iranian journals of Nursing and Midwifery, based on the PRISMA statement. Methods & Materials: In this study, we conducted a comprehensive search on the Iranian journals of Nursing and Midwifery (Persian and English), indexed by the SID, Magiran, Irandoc, Iranmedex and Google Scholar databases during 2010 to 2015 years. The search was implemented using the key words such as systematic review and meta-analysis. Of the 44 articles found, after considering the inclusion criteria, 16 articles remained that were investigated using the PRISMA statement. Data were analyzed through the descriptive statistics and chi-square test using SPSS software version 16. Results: The compliance rate of studies on the basis of PRISMA statement was estimated to be about 63%. The most common deficiency in the reporting quality was related to methodology estimated to be about 57%. The most visible deficiencies in the reporting of systematic reviews and meta-analysises were related to bias in the primary studies and bias in combining the results of these studies and lack of reporting these biases. Conclusion: In this study, the reporting quality of systematic reviews and meta-analysises in the Iranian journals of nursing and midwifery was in the moderate level. The most probable reason for this may be the lack of enough attention of researchers to the PRISMA statement or not using this statement in reviewing articles. Therefore, it is recommended that an appropriate share of the educational programs on research methodology be allocated to systematic reviews and familiarizing with valid criteria such as PRISMA statement.